1986
DOI: 10.2135/cropsci1986.0011183x002600030020x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Locations for Heading Date Using Reciprocal Chromosome Substitutions in Winter Wheat1

Abstract: Heading date, which is one of the developmental stages of wheat (Tritlcum aestivum L.) that contribute to maturity, is therefore significant trait from an economic standpoint. Reciprocal sets of chromosome substitution lines in duplicate between two hard red winter wheat cultivars, Cheyenne and Wichita, were used to identify chromosomes that carried genes for heading date. The materials were planted in the field at Lincoln, NE using a randomized complete block design with three replications. Heading dates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Moreover, chromosome-specific recombinant inbred lines (RILs) or recombinant substituted (RS) lines can be used to separate, identify, and map gene(s) controlling agronomic traits and fiber traits by linkage with molecular markers (Kaeppler 1997;Shah et al 1999). Studies have demonstrated the advantages of QTL mapping using chromosome substitution and chromosome-specific recombinant lines in wheat, tomato, and mice (Zemetra et al 1986;Zemetra and Morris 1988;Yen and Baenziger 1992;Weide et al 1993;Shah et al 1999;Nadeau et al 2000;McDonald et al 2001). Indeed, we are developing RS populations to be used for high-resolution dissection and mapping of the QTL governing cotton yield and fiber qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chromosome-specific recombinant inbred lines (RILs) or recombinant substituted (RS) lines can be used to separate, identify, and map gene(s) controlling agronomic traits and fiber traits by linkage with molecular markers (Kaeppler 1997;Shah et al 1999). Studies have demonstrated the advantages of QTL mapping using chromosome substitution and chromosome-specific recombinant lines in wheat, tomato, and mice (Zemetra et al 1986;Zemetra and Morris 1988;Yen and Baenziger 1992;Weide et al 1993;Shah et al 1999;Nadeau et al 2000;McDonald et al 2001). Indeed, we are developing RS populations to be used for high-resolution dissection and mapping of the QTL governing cotton yield and fiber qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Genes for ear-emergence per se on 3A (Kosner, 1987;Miura & Worland, 1994). 3A and 3B also efTect earemergence (Zemetra, Morris & Schmidt, 1986) Genes on 4A and 4B affecting ear-emergence per se (Hoogendoorn, 1985) Major genes on the long arms, sensitive to vernalization.…”
Section: Locationsmentioning
confidence: 99%
“…Chromosome substitution lines have been used to identify the chromosome associations with traits of importance in wheat and other crops (Berke et al, 1992;Al-Qaudhy et al, 1988;Zemetra and Morris, 1986;Zemetra et al, 1988). Kohel et al (1977) and Ma and Kohel (1983) evaluated six cotton substitution lines and indicated some quantitative genes on the substituted chromosomes.…”
Section: Introductionmentioning
confidence: 99%